An algebraic theory for modeling direct interconnection networks - Kaushik, S.D.; Sharma, S.; Huang, C.-H.; Johnson, J.R.; Johnson, R.W.; Sadayappan, P. (Supercomputing, `92, 1992)
The authors present an algebraic theory based on tensor products for modeling direct interconnection networks. This theory has been used for designing and implementing block recursive numerical algorithms on shared-memory vector multiprocessors. This theory can be used for mapping algorithms expressed in tensor product form onto distributed-memory architectures. The authors focus on the modeling of direct interconnection networks. Rings, n-dimensional meshes, and hypercubes are represented in tensor product form. Algorithm mapping using tensor product formulation is demonstrated by mapping matrix transposition and matrix multiplication onto different networks.< >